Asymmetric Compassion Collapse, Collateral Consequences, and Reintegration: An Experiment. (2nd December 2022) - Novick, Rachel; Socia, Kelly M.; Pickett, Justin T.
Abstract: Public opinion is doubly important for reintegration, as it shapes both the policy and the stigma environments that people with criminal records must face. Nowhere are the policy and stigma environments bleaker than for record holders convicted of sex crimes. Drawing on the theory of compassion collapse (or psychic numbing) and using experimental data from a national survey, we examine the effects of informing members of the public about the hardships faced by record holders convicted of sex crimes, and we compare those effects (or the lack thereof) to the effects of victim discourse. We also randomize the information format: aggregate/statistical versus personal narratives. We find that narratives about crime victims' suffering matter to the public—increasing aversive emotions, support for collateral consequences, and stigmatization—but narratives about record holders' suffering do not. We conclude by discussing alternative communication strategies that public criminologists may use to garner public support for progressive criminal justice reforms.